Specificity of Cognate Nouns and Adjectives Functioning - L. V. Noskina (Дискурс, 2020)
Introduction. The aim of the article is to determine whether syntactic behavior of linguistic unit depends on its part-of-speech identity or only its semantics. The importance of the research is determined by the absence of systematic description of the specificity of cognate words functioning in linguistics.Methodology and sources. The research deals with the cognate nouns and adjectives functioning. According to the classification of semantic types of predicates developed by A. G. Eliseeva, O. N. Seliverstova we define the researched predicates as the ones denoting state. These predicates are studied in terms of case grammar, i. e. they are compared in the aspect of an argument structure realization. In determining the semantic cases of predicates, we mainly rely on the set of semantic cases proposed by V. V. Bogdanov.Results and discussion. It is shown that the analyzed nouns, as a rule, expressing given or known information require a lower number of cases in its explicit forms which still can be implicit. The researched adjectives that usually denote new information are accompanied by a higher number of cases in a surface structure. These predicates also differ in the forms of their arguments.Conclusion. The revealed features of cognate nouns and adjectives functioning show the significant influence of the form of linguistic unit on syntactic behavior and indicate that formation of syntactic structures is not only determined by semantics.